The Development of Soft Skills through Music in Educational Contexts: A Systematic Review - Mario Diz-Otero; Margarita Pino-Juste; Jose María Esteve-Faubel; Sara Domínguez-Lloria (Education Sciences, 2023)
Numerous scientific studies confirm that music is a tool to improve and develop interpersonal skills. These skills, such as leadership, teamwork, communication, interpersonal skills, or coordination. are essential at present and their acquisition is necessary to adapt to a constantly changing society. The aim of this study is to analyze the contribution of music to the development of soft skills in educational contexts. To achieve the objective of the study, a systematic review of the last five years was carried out to find the existing empirical evidence. Among the main results, we observed that soft skills improve when they are developed through music in educational contexts, concluding that educational interventions with music allow for participants to develop these skills.